THE SCHOOL FOR TEENAGERS: SIGNIFICATIONS AND MEANINGS DURING THE PANDEMIC - Luana Mundim de Lima; Anabela Almeida Costa e Santos Peretta; Carmen Lúcia Reis; Maria Paula Cunha Souza Carrijo Pereira; Yasmim Marques de Souza (Psicologia em Estudo, 2025)
This qualitative research aimed to understand and discuss, from the Historical-Cultural Theory, what meanings are attributed to school by adolescents from private and public schools in Uberlândia-MG during the COVID-19 pandemic. Nine high school students between 15 and 18 years old participated. Between September and October 2020, we carried out individual semi-structured interviews, remotely. Through content analysis, we built five categories about the functions assigned to schools by adolescents: 1) Space for socialization and preparation for life; 2) Content learning context; 3) Space for academic and professional (un)preparation; 4) Organizing place; 5) Support space. However, especially for students in public schools, the fulfillment of most of these roles is being insufficiently carried out during the pandemic, revealing the inequalities and injustices involved in access to education. Furthermore, the importance of guaranteeing the right to schooling for the integral development of adolescents is highlighted, providing for the appropriation of knowledge and critical reflection on reality.